Impact of the JET ITER-like wall on H-mode plasma fueling. (26th April 2017) - Wiesen, S.; Brezinsek, S.; Wischmeier, M.; De la Luna, E.; Groth, M.; Jaervinen, A. E.; de la Cal, E.; Losada, U.; de Aguilera, A.M.; Frassinetti, L.; Gao, Y.; Guillemaut, C.; et al.
Abstract: JET ITER-like wall (ILW) experiments show that the edge density evolution is strongly linked with the poloidal distribution of the ionization source. The fueling profile in the JET-ILW is more delocalized as compared to JET-C (JET with carbon-based plasma-facing components PFCs). Compared to JET-C the H-mode pedestal fueling cycle is dynamically influenced by a combination of plasma–wall interaction features, in particular: (1) edge-localized modes (ELMs) induced energetic particles are kinetically reflected on W divertor PFCs leading to distributed refueling away from the divertor depending on the divertor plasma configuration, (2) delayed molecular re-emission and outgassing of particles being trapped in W PFCs (bulk-W at the high field side and W-coated CFCs at the low field side) with different fuel content and (3) outgassing from Be co-deposits located on top of the high-field side baffle region shortly after the ELM. In view of the results of a set of well diagnosed series of JET-ILW type-I ELMy H-mode discharges with good statistics, the aforementioned effects are discussed in view of H-mode pedestal fueling capacity. The ongoing modelling activities with the focus on coupled core-edge plasma simulations and plasma–wall interaction are described and discussed also in view of possible code improvements required.